P PRAKTIK MAKELAR PADA JASA PEMESANAN KAOS DI AL-ASYHAR CLOTH JOGOROTO JOMBANG PERSPEKTIF HUKUM EKONOMI SYARIAH: BROKER PRACTICES IN T-SHIRT ORDERING SERVICES AT AL-ASYHAR CLOTH JOGOROTO JOMBANG PERSPECTIVE SHARIA ECONOMIC LAW - Azizi Fahmi; Islami, Trinah Asi (Irtifaq, 2025)
This Article discusses broker practices in T-shirt ordering services at Al-Asyhar Cloth, Jogoroto Village, District. Jogoroto, Kab. Jombang. The ijarah contract agreement between the Al-Asyhar Cloth business owner and the broker is carried out verbally. The research method used is an empirical juridical method with a conceptual approach. This data collection uses observation, interview, documentation and library data techniques. The data analysis technique used is inductive and descriptive methods. The research results show that brokering practices in the Al-Asyhar cloth t-shirt ordering service involve sellers and brokers. The mechanism that occurs is that Al-Asyhar Cloth asks brokers to sell or market convection goods in the shop. However, in providing wages, Al-Asyhar Cloth did not fulfill its obligations in accordance with the initial agreement which stipulated 10% of total sales, but instead provided them in stages of 5%. From the results of the broker's practice at Al-Asyhar Cloth, Sharia Economic Law states that renting the benefits (services) of the broker's work is allowed. However, in this case, not fulfilling the initial agreement by Al-Asyhar Cloth is considered impermissible because it contains elements of injustice in fulfilling rights and obligations which are contrary to Islamic beliefs